Assessment of Dietary Habits and Dietary Factors Related to Self-rated Health and Diet-related Quality of Life of Fourth-, Fifth-, and Sixth-grade Elementary Schoolboys Participating in Junior Soccer Clubs - Oka, Jun; Inayama, Takayo; Otaki, Hiromi; Nishikawa, Seidai (Eiyōgaku zasshi, 2012)
Objective: The objective of this study is to assess dietary habits as a whole and determine which dietary factors correlate with the self-rated health and diet-related quality of life (QOL) of fourth-, fifth-, and sixth-grade elementary schoolboys who participate in junior soccer clubs. Methods: The subjects included 75 elementary schoolboys (valid response rate, 93%). A self-administered questionnaire was used in the study, and its framework included questions regarding QOL, health and nutrition status, behavior, stage of change, preparation factor, attribute, dietary environment, and relation between exercise and nutrition. To determine which diet-related factors are correlated with QOL, binomial logistic regression analysis was performed using QOL as the dependent variable and other factors as the independent variables. Results: On assessing dietary habits according to the questionnaire framework, many responses were sorted into the categories of high QOL level, eating behavior, staple food-related preparation factors, and dietary environment. Not many positive responses were obtained for meal planning and preparation or for sharing and applying diet-related information. The binomial logistic regression analysis performed with QOL as the dependent variable showed that the QOL was significantly associated with “the frequency of eating dinner with the family,” “telling the parents to prepare healthy food,” “outcome expectancy for eating rice sufficiently,” “self-efficacy for eating rice sufficiently,” “motivation for diet-related learning,” and “the frequency of eating snacks after exercise.” Conclusions: Dietary education programs for elementary school children who participate in sports activities need to set goals for encouraging specific eating behavior that enhances the students' preparation factors and for planning interventions that include sports activity.